Efficient degradation of ciprofloxacin via peroxymonosulfate activation over a hierarchically porous Cu-Ti alloy manufactured by 3D printing - Guo, Sheng (2024)
3D printed alloy catalysts have garnered significant attention in water purification due to their high efficiency, adaptable structure, and easy recovery. Here, a straightforward and cost-effective three-dimensional (3D) printing strategy is adopted to synthesize a copper-titanium (Cu-Ti) alloy for ciprofloxacin (CIP) degradation through peroxymonosulfate (PMS) activation. The resulting 3D Cu-Ti alloy, characterized by a hierarchical porous structure, exhibits the highest removal efficiency of 90.55% for CIP degradation, surpassing that of commercial Cu and Ti powders under similar conditions. Capture experiments and electron paramagnetic resonance measurements reveal the involvement of •OH, 1O2, SO4•-, and O2•- in the degradation of CIP, with •OH and 1O2 playing dominant roles. The presence of Ti not only promotes Cu(I)/Cu(0) and Cu(II)/Cu(I) cycling but also facilitates the activation of dissolved oxygen in water, thereby reducing its reaction with PMS and preventing corrosion, ultimately rendering the 3D-Cu-Ti/PMS alloy excellent catalytic activity and reusability. Additionally, bean sprout growth experiments indicate a remarkable reduction in the toxicity of CIP degradation products. The utilization of 3D printing technology for the construction of a Cu-Ti alloy offers a promising strategy for the removal of CIP through PMS activation.